Teori Pemodelan Bandura - Ansani; H. Muhammad Samsir (Jurnal Multidisiplin Madani, 2022)
The purpose of this research is to observe, Albert Bandura's social learning theory modeling, and the implementation of Albert Bandura's modeling of social learning model in learning. Albert Bandura's form of social learning is that individuals process their own knowledge or information obtained from observing models around the environment. Individuals organize and organize all information in certain codes. The process of compiling each code is repeated, so that individuals can provide actual responses at any time. The learning process by applying social learning methods is not a new approach to the teaching and learning process, but is already known and popular, it's just that it is often forgotten. What is meant by applying social learning methods in the learning process is learning by utilizing the social environment as learning targets, learning resources, and learning tools. On the basis of these assumptions, Albert Bandura's learning theory is called social cognitive because cognitive processes in individuals play a role in learning, while learning occurs because of the influence of the social environment. The process of stages in cognitive social learning includes: the attentional phase, the retention phase, the reproduction phase and the motivation phase